2003
DOI: 10.1046/j.1365-3059.2003.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on ascospore germination and penetration of oilseed rape (Brassica napus) leaves by A‐ or B‐groupLeptosphaeria maculans(phoma stem canker)

Abstract: Ascospores of both A‐group and B‐group Leptosphaeria maculans germinated at temperatures from 5 to 20°C on leaves of oilseed rape. Germination of ascospores of both groups started 2 h after inoculation and percentage germination reached its maximum about 14 h after inoculation at all temperatures. Both the percentage of A‐/B‐group ascospores that had germinated after 24 h incubation and germ tube length increased with increasing temperature from 5 to 20°C. Germ tubes from B‐group ascospores were longer than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 26 publications
(53 reference statements)
5
39
1
Order By: Relevance
“…Temperature is also critical for the expression of some resistance to L. maculans in B. napus, with, for example, a lesser efficiency of the Rlm6 resistance at temperatures above 25°C (Huang et al, 2006). We have established that the temperature also influences the transcription level of effectors and the optimum of 16°C coincides with the range of optimal temperatures previously reported for ascopore germination and leaf lesion development (Huang et al, 2003). For oilseed rape, an apoplastic pH of 5.8 and an ammonium concentration of 1.3 mM were measured in young leaves of B. napus cv Global but not data for sugar concentrations are currently available (Husted and Schjoerring, 1995).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Temperature is also critical for the expression of some resistance to L. maculans in B. napus, with, for example, a lesser efficiency of the Rlm6 resistance at temperatures above 25°C (Huang et al, 2006). We have established that the temperature also influences the transcription level of effectors and the optimum of 16°C coincides with the range of optimal temperatures previously reported for ascopore germination and leaf lesion development (Huang et al, 2003). For oilseed rape, an apoplastic pH of 5.8 and an ammonium concentration of 1.3 mM were measured in young leaves of B. napus cv Global but not data for sugar concentrations are currently available (Husted and Schjoerring, 1995).…”
Section: Discussionsupporting
confidence: 80%
“…Temperature is an important parameter for germination of ascospores of L. maculans as well as germ tube elongation on leaf surfaces and for the formation of leaf lesions (Toscano-Underwood et al, 2001;Huang et al, 2003). In controlled-environment experiments performed with increasing temperature from 5°C to 20°C, optimal temperatures of 15-20°C were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (2003) compared the germination and penetration by ascospores of A-group and B-group of L. maculans on winter-type B. napus. Toscano-Underwood et al (2001) reported the development of blackleg lesions on oilseed rape leaves inoculated with ascospores of A-group and B-group.…”
Section: Introductionmentioning
confidence: 99%
“…complex to different temperatures; this parameter affected maturation of pseudothecia of L. maculans and L. biglobosa on oilseed rape stem debris. Moreover, Huang et al (2003) indicated that temperature affected ascospore germination and penetration of leaves of oilseed rape, which further demonstrates the importance of weather parameters on pathogen development. Recognition of relationships between weather parameters and pathogen development has allowed the construction of mathematical models for the prediction of the onset of pseudothecia maturity (Salam et al 2003) and seasonal ascospore showers (Salam et al 2007).…”
Section: Resultsmentioning
confidence: 83%